Dna extraction from tropical fruit trees. - N. M., Saleh; R., Muse (2001)
Tropical plants have been notoriously known to be rich in polyphenolic compounds, polysaccharides and other complex substances which normally interfere with the process ofplant DNA extraction, thus resulting in small amount of 'unclean' DNA being extracted The methods described here, however, were able to extract reasonable amount o!,clean' DNA from field grown leaves of tropical fruit trees (Achras sapota L. and Durio zibethinus Murr.); yet it is an efficient and inexpensive method. Thus, allowing for large number of samples to be extracted.